Perkawinan Adat Urak Tanah Ulu Muarasipongi : Perspektif Hukum Islam - Aminudin, Aminudin; Irham, Muhammad Iqbal; Zein, Achyar (Universitas Islam Sumatera Utara, 2024)
This study describes the traditional marriage of Urak Tanah Ulu Muarasipong from the perspective of Islamic law. The Urak Tanah Ulu Muarasipongi marriage ritual uses the expression, firstly kawinan Sumendo which means that the man does not offer the dowry to the woman, but the woman offers and gives the dowry to the man. Urak Tanah Ulu Muarasipongi, the dowry given to men is called “pick-up money”. Second, tobenda marriage (wasted marriage), which is a marriage that comes from one descendant. Couples who are expelled from the village will only be able to return to the community if they have paid a fine. The amount of the fine is determined based on the decision of the adat deliberation. The fine is quite large, even this Tobenda marriage couple cannot pay it, because the community itself does not want to accept the couple back. Qualitative research methods were used to obtain information about customary marriage in Urak Tanah Ulu through collecting data, observation, and interviews. The results show that first, the tradition of Sumendo women proposing marriage to men is motivated by cultural and social factors. They believe that the long-established tradition can influence a woman's obedience to her husband and this is considered good. Second, Tobenda marriage, the Urak Tanah Ulu community considers inter-tribal marriage a taboo marriage, they consider people of the same tribe to have the same blood and descent. Keywords: Marriage, Urak Tanah Ulu, Kawin Sumendo, Kawin Tobenda, Islamic Law